Reticulocyte Hemoglobin (Ret-He) Accuracy as A Diagnostic Parameter in Detecting Iron Deficiency Anemia in Children. - Dedianto, Dedianto; Sari, Dian Puspita; Bakri, Achirul; Bahar, Erial; Ayu, Dewi Rosalia (Innovative: Journal Of Social Science Research, 2025)
Reticulocyte hemoglobin (Ret-He) is a parameter used to assess the amount of hemoglobin in reticulocyte, thus Ret-He describes the mean of hemoglobin content distribution in the reticulocyte, so that the Ret-He examination can be used as a parameter to diagnose iron deficiency anemia early. Screening of IDA which are cheap and easy is still needed. To analyze whether Ret-He can be a parameter in determining iron deficiency anemia in children. This study is a diagnostic test study. The research data was obtained from outpatient and outpatient laboratory data that showed hypochromic microcytic anemia from July to October 2017 in Department of Pediatrics Moh. Hoesin Hospital Palembang. Data analysis was done using SPSS software. The result of research done by comparison between Ret-He value and transferin saturation value (gold standard). The total number of 120 subjects consisted of 52 subjects in IDA group (TfSat <15%) and 68 subjects in non-IDA group (TfSat ≥15%). The IDA incidence of hypochromic microcytic anemia group in Moh.Hoesin Hospital is 43.3%. The best cut off point of Ret-he is 21.95pg. Based on calculation by using Cut off point 21,95pg, the data obtained NDP 97,8%, NDN 90,5%, RKP 57,6, RKN 0,13 and AUC value 99,8%. Ret- He can be used as a method to detect ID is easy and cheap